The interplay of community attitudes, local development, and personal benefits: understanding support for the China–Pakistan Economic Corridor - Jun, Yang; Khan, Shahrukh; Hena, Sehresh; Khalil, Inam Ullah; Raza, Muhammad Haseeb; Cui, Baoyu (Frontiers in Sustainable Food Systems, 2025)
Large-scale infrastructure projects like the China–Pakistan Economic Corridor (CPEC) are often promoted as catalysts for local community development, economic growth, and enhanced social wellbeing. Although CPEC offers considerable potential advantages for Pakistani communities, gaining insight into local perceptions remains an important research gap. This study investigates the determinants of local community support for CPEC development. Using a structured research model, data from 771 survey respondents across Pakistan were analyzed using Structural Equation Modeling (SEM) in AMOS 24.0. The findings reveal that CPEC-related infrastructure development positively correlates with perceived community development, overall community attitude, and quality of life. Crucially, community development significantly shapes overall community attitude toward CPEC, while improvements in quality of life do not exhibit a direct, significant effect on this attitude. Furthermore, a positive overall community attitude strongly predicts increased support for CPEC. A pivotal finding is the significant moderating role of personal benefit; the relationship between overall community attitude and support for CPEC development is significantly strengthened when individuals perceive greater personal gains from the project. This research underscores the importance of aligning large-scale infrastructure initiatives like CPEC with local community needs and perceptions, emphasizing that fostering tangible community development and ensuring residents perceive personal benefit are vital for garnering sustainable local support. The study discusses implications for policymakers and project planners, limitations, and directions for future research to better capture community dynamics in major infrastructure undertakings.